Sustainable computing workshops in high-energy physics at DESY - Alimena, Juliette; Beyer, Christoph; Brüers, Ben; Gaede, Frank; Gillwald, Nils; Hernandez Villanueva, Michel; Jones, Eleanor; Kemp, Yves; Madlener, Thomas; Schwarz, Kilian; Wissing, Christoph (Frontiers in Computer Science, 2024)
This perspective article details the program of sustainable computing workshops launched within the High Energy Physics department at Deutsches Elektronen-Synchrotron (DESY) in 2023. The workshop series targets scientific users of the National Analysis Facility, hosted at DESY, in order to promote sustainable software development and usage across a wide range of applications. Details of the structure of the workshops, as well as the reception amongst participants, will be presented. In addition, plans for the expansion of the workshop series will be outlined.